Structural change and spurious persistence in stochastic volatility - Krämer, Walter; Messow, Philip (Technische Universität Dortmund, 2011)
We extend the well established link between structural change and estimated persistence from GARCH to stochastic volatility (SV) models. Whenever structural changes in some model parameters increase the empirical autocorrelations of the squares of the underlying time series, the persistence in volatility implied by the estimated model parameters follows suit. This explains why stochastic volatility often appears to be more persistent when estimated from a larger sample as then the likelihood increases that there might have been some structural change in between.
Discussion Paper / SFB 823;48/2011
Keywords: persistence; stochastic volatility; structural change; 310; 330; 620